Amphibious Inventory in Borneo Indonesia Through the AMNH Platform - Heafiz, Elviona; zega, Dwi; Hayyat, Rafikul; Utia, Ulta; Satria, Rijal; Nugraha, Fitra (Department of Biology, Faculty of Mathematics and Natural Sciences, Universitas Negeri Padang, 2024)
Borneo is the 3rd largest island in the world with an area of 748,168 km2. Indonesia which has a high biodiversity value. Amphibians are one of the constituent components of the ecosystem that has a very important role. This study aims to determine the number and diversity of amphibians on the island of Kalimantan. This research was conducted by collecting data through the AMNH (Amphibian Museum of Natural History) Platform. Based on data collected through the AMNH platform, there were 10 families, namely Megophryidae as many as 13 species, Mycrohilidae as many as 16 species, Ranidae as many as 19 species, Dicroglossidae as many as 15 species, Bombinatoridae as many as 2 species, Ichthyophiidae as many as 2 species, Ceratobatrachidae as many as 2 species, Bufonidae as many as 6 species, and Rhacophoridae as many as 16 species. So the total amphibians on the island of Borneo based on the data we obtained through the AMNH platform is 91 species.